2023
DOI: 10.1007/s00467-022-05872-z
|View full text |Cite
|
Sign up to set email alerts
|

Rejection markers in kidney transplantation: do new technologies help children?

Abstract: Recent insights in allorecognition and graft rejection mechanisms revealed a more complex picture than originally considered, involving multiple pathways of both adaptive and innate immune response, supplied by efficient inflammatory synergies. Current pillars of transplant monitoring are serum creatinine, proteinuria, and drug blood levels, which are considered as traditional markers, due to consolidated experience, low cost, and widespread availability. The most diffuse immunological biomarkers are donor-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 83 publications
(104 reference statements)
0
7
0
Order By: Relevance
“…Of note, early reports indicate that 17% of samples failed quality control, 73 a problem that highlights the methodological challenges of urinary mRNA, which tends to degrade without proper sample processing and storage even with high level of technical training. 74…”
Section: Allomap Kidney (Caredx) the Transplant Genomics Collaborativementioning
confidence: 99%
See 1 more Smart Citation
“…Of note, early reports indicate that 17% of samples failed quality control, 73 a problem that highlights the methodological challenges of urinary mRNA, which tends to degrade without proper sample processing and storage even with high level of technical training. 74…”
Section: Allomap Kidney (Caredx) the Transplant Genomics Collaborativementioning
confidence: 99%
“…Six hundred children are expected to be followed prospectively for 12 months with longitudinal urine testing and biopsies including for‐cause and surveillance. Of note, early reports indicate that 17% of samples failed quality control, 73 a problem that highlights the methodological challenges of urinary mRNA, which tends to degrade without proper sample processing and storage even with high level of technical training 74 …”
Section: Transcriptomicsmentioning
confidence: 99%
“…Drug level monitoring is an important biomarker for assessing the proper use of immunosuppressive drugs in transplant recipients. It is commonly performed for drugs such as tacrolimus, cyclosporine, everolimus, and sirolimus [ 195 ]. However, monitoring mycophenolic acid (MPA) using single-sample drug concentrations in the recipient’s blood immediately before the next dose is administered may not accurately reflect the overall drug exposure.…”
Section: Immune Tolerance and Therapeutic Drug Monitoringmentioning
confidence: 99%
“…To overcome this limitation, MPA area under the curve estimation has been introduced as a more effective clinical tool. However, it requires multiple concentration samplings, which can be less practical, especially in pediatric patients [ 195 , 196 ].…”
Section: Immune Tolerance and Therapeutic Drug Monitoringmentioning
confidence: 99%
“…It should be noted that, since EV markers are not the focus of this review, the table here is not meant to be a complete list of all the markers reported in literature. We suggest readers to refer to other review articles for more thorough discussion of the various disease types and their potential EV markers. , …”
Section: Biomarkers For Evsmentioning
confidence: 99%